If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + -2(4 + -2p) = 19 5p + (4 * -2 + -2p * -2) = 19 5p + (-8 + 4p) = 19 Reorder the terms: -8 + 5p + 4p = 19 Combine like terms: 5p + 4p = 9p -8 + 9p = 19 Solving -8 + 9p = 19 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 9p = 19 + 8 Combine like terms: -8 + 8 = 0 0 + 9p = 19 + 8 9p = 19 + 8 Combine like terms: 19 + 8 = 27 9p = 27 Divide each side by '9'. p = 3 Simplifying p = 3
| Y=-2+-0.6666666667x | | -3/7w=9 | | 2x-(2-x)=13 | | x=(2m-4)/(1+n) | | 125^-2/3 | | 7x^2+40x+25=0 | | 9x-8x-10=13 | | 9.05=8.2 | | 3[8y+2]=10y+2[7y+3] | | 5/12=6/x | | 9+9-1-2+5m-1-4m=32 | | t*5=54 | | 3x-(5+2x)= | | x+4x-73=72 | | 10/3x2/5 | | 5x+16=2X | | 6x/3-18 | | 3/10(220) | | 2-3t+6+4t-12=9t | | 3c+8=5c+11 | | 2n+8=17 | | 555,555,555+124,135,352,246= | | 3Q-1+10-4+1-1-2=20 | | (1/3)*3(1/4) | | f(2)=3(2) | | 3.50t+5.50=51 | | -7n+10=4n+10 | | 3.60.+s=3 | | (3/5*x)-(2/3)=1 | | -4(-7x+1)+5(8+2x)=-2 | | -1/2z=-10 | | 18=3s |